RNA Interference - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2016)
RNA interference (RNAi), a hallmark of all biological sciences of twenty-first century, is an evolutionarily conserved and double-stranded RNA-dependent eukaryotic cell defense process. Opportunity to utilize an organisms own gene and to systematically induce and trigger RNAi for any desired sequence made RNAi an efficient approach for functional genomics, providing a solution for conventional longstanding obstacles in life sciences. RNAi research and application have significantly advanced during past two decades. This book RNA interference provides an updated knowledge and progress on RNAi in various organisms, explaining basic principles, types, and property of inducers, structural modifications, delivery systems/methodologies, and various successful bench-to-field or clinic applications and disease therapies with some aspects of limitations, alternative tools, safety, and risk assessment.